The study of satisfaction on third-party logistics (3PL) service in automotive industry : a case study in Pekan, Pahang - Mohamad Husaini, Badrul Zaman (2014)
This dissertation explores the topic of Supply Chain (SC), an important topic that captured attention of practitioner, journals and the business press. The focus of this research is on customer satisfaction of implementing Third-Party Logistics (3PL) services in automotive industry relative to the impact of the company’s ﬁnancial performance. This research been conducted to study the relationship of 3PL implementation efficiency and company performance, and the most signiﬁcant factors inﬂuences the efﬁciency of ﬁnancial performance was examined. To investigate the relationship of 3PL implementation efficiency and company performance. To identify the most signiﬁcant factor of 3PL implementation efficiency towards efficiency of ﬁnancial performance of implementing 3PL. A quantitative analysis been conducted using SPSS 22 generating results on investigation of 3PL service efﬁciency towards efﬁciency of ﬁnancial performance. The results shows all selected independent variables (IV) has strong linear relationship towards dependent variable (DV) providing service quality as the most signiﬁcant factor of 3PL implementation towards efficiency of ﬁnancial performance of implementing 3PL. In this study, it proves that implementing 3PL services do increased the companies ﬁnancial performance. 3PL providers especially who provide service to automotive industry should focus on service quality because it has the most impact inﬂuence customer satisfaction. For recommendations, the all companies (especially automotive industries) are recommended to implement external logistics services (3PL, 4PL and etc.) in their operations or processes. Future researcher could use the same framework to explore different industry